The Impact of Geopolitical Risk on Consumer Expectations and Spending - Yuriy Gorodnichenko; Dimitris Georgarakos; Geoff Kenny; Olivier Coibion (Institute of Labor Economics (IZA), 2025)
Using novel scenario-based survey questions that randomize the expected duration of the Russian invasion of Ukraine and Middle East conflict, we examine the causal impact of geopolitical risk on consumers' beliefs about aggregate economic conditions and their own financial outlook. Expecting a longer conflict leads European households to anticipate a worsening of the aggregate economy, with higher inflation, lower economic growth, and lower stock prices. They also perceive negative fiscal implications, anticipating higher government debt and higher taxes. Ultimately, households view the geopolitical conflict as making them worse off financially and it leads them to reduce their consumption.
Keywords: D1; E2; E3; F5; 330; geopolitics; international conflicts; war; risk; expectations; Consumer Expectations Survey